2014
DOI: 10.1590/s1415-47572014005000015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of indica and japonica rice varieties

Abstract: Indica and japonica are two main subspecies of Asian cultivated rice (Oryza sativa L.) that differ clearly in morphological and agronomic traits, in physiological and biochemical characteristics and in their genomic structure. However, the proteins and genes responsible for these differences remain poorly characterized. In this study, proteomic tools, including two-dimensional electrophoresis and mass spectrometry, were used to globally identify proteins that differed between two sequenced rice varieties (93–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…indica . The japonica varieties are adapted to more temperate climates, whereas most indica varieties are generally adapted to tropical lowland cultivation [2]. The distinction between the two rice subspecies has been recognized in China since at least the Han dynasty [3].…”
Section: Introductionmentioning
confidence: 99%
“…indica . The japonica varieties are adapted to more temperate climates, whereas most indica varieties are generally adapted to tropical lowland cultivation [2]. The distinction between the two rice subspecies has been recognized in China since at least the Han dynasty [3].…”
Section: Introductionmentioning
confidence: 99%
“…The expression pattern of majority of these genes at the transcript level showed consistency with the protein expression, confirming their differential expression during R. solani infection. Earlier study in rice showed consistency of genes expression with proteomic analysis (Yang et al, 2014). Few genes did not show the desired consistency with protein expression level which might be due to several regulatory processes of these genes such as mRNA stability, splicing, post-transcriptional gene regulation, translational regulation, and protein degradation, as reported earlier by Liao et al (2013).…”
Section: Discussionmentioning
confidence: 70%
“…japonica is mainly found in temperate regions with high latitudes, whereas subsp. indica is mostly cultivated in tropical and subtropical rice planting regions (Yang et al 2014). The fast development of whole genome sequencing technology and the application of bioinformatics have made it possible to explore genetic differentiation between Indica and Japonica rice.…”
Section: Discussionmentioning
confidence: 99%